2001
DOI: 10.1007/s005860100315
|View full text |Cite
|
Sign up to set email alerts
|

Microendoscopic lumbar discectomy versus open surgery: an intraoperative EMG study

Abstract: This study investigated electromyographic (EMG) activity as a marker of nerve root irritation during two different surgical procedures for lumbar disc herniation. Mechanically elicited EMG activity was recorded during the dynamic stages of surgery in muscle groups innervated by lumbar nerve roots. Confirmation of surgical activity was correlated with the activity of the electromyogram. Fifteen patients with lumbar disc herniations were treated via an endoscopic medial approach, and 15 patients via the open mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 21 publications
0
85
0
4
Order By: Relevance
“…11-14,30, [32][33][34][35]37 However, because these studies involved small numbers of patients in single institutions, it remains unclear whether MED is truly a safer technique than open discectomy. Despite the clinical importance of understanding the risk for adverse surgical comorbidities, few nationwide studies have examined these issues by directly comparing MED and open discectomy.…”
mentioning
confidence: 99%
“…11-14,30, [32][33][34][35]37 However, because these studies involved small numbers of patients in single institutions, it remains unclear whether MED is truly a safer technique than open discectomy. Despite the clinical importance of understanding the risk for adverse surgical comorbidities, few nationwide studies have examined these issues by directly comparing MED and open discectomy.…”
mentioning
confidence: 99%
“…A comparative study of METRx with conventional microdiscectomy showed a significant faster return to work for the new procedure [12]. Furthermore, an intraoperative EMG-study done by Schick demonstrated that the transmuscular route damages the paraspinal muscles less than the subperiostal approach [14]. This is in accordance with the observation of Kim et al, which reported a decrease of the cross sectional area of spinal muscles on MRI after open pedicle screw fixation, but no decrease after use of percutaneous pedicle screw osteosynthesis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported a better and more rapid recovery with the minimal muscular manipulation during spinal surgery. The MED has been associated with reduced paraspinal muscle damage compared to the conventional subperiosteal approach using a serological marker such as CPK-MM 18) , or intraoperative electromyography evaluations 17) . Brock et al 4) reported that compared to the conventional subperiosteal approach, the transmuscular approach required reduced amounts of analgesics during the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%